Cationic Carbon Nanoparticles Induce Inflammasome-Dependent Pyroptosis in Macrophages via Lysosomal Dysfunction - Arezki, Yasmin; Rapp, Mickaël; Lebeau, Luc; Ronzani, Carole; Pons, Françoise (Frontiers in Toxicology, 2022)
Carbon nanomaterials, including carbon dots (CDs), form a growing family of engineered nanoparticles (NPs) with widespread applications. As the rapid expansion of nanotechnologies raises safety concerns, interaction of NPs with the immune system is receiving a lot of attention. Recent studies have reported that engineered NPs may induce macrophage death by pyroptosis. Therefore, this study investigated whether cationic CDs induce pyroptosis in human macrophages and assessed the role of inflammasome and lysosome in this process. Cationic CDs were synthetized by microwave-assisted pyrolysis of citric acid and high molecular weight branched polyethyleneimine. The NPs evoked a dose-dependent viability loss in THP-1-derived macrophages. A cell leakage, an increase in IL-1β secretion and an activation of caspase-1 were also observed in response to the NPs. Inhibition of caspase-1 decreased CD-induced cell leakage and IL-1β secretion, while restoring cell viability. Besides, CDs triggered swelling and loss of integrity of lysosome, and inhibition of the lysosomal enzyme cathepsin B decreased CD-induced IL-1β secretion. Thus, our data provide evidence that cationic CDs induce inflammasome-dependent pyroptosis in macrophages via lysosomal dysfunction.